Teacher’s Role in Managing the Classroom Pedagogy (Shaheed Smriti Journal, 2023)
The purpose of this research is to investigate teacher’s roles performed by the English teachers in managing the class during the teaching and learning process at schools of Ratnanagar municipality. The research methodology used is descriptive design with qualitative approach which is aimed to describe the real situation in the field. In collecting the data, the researchers used questionnaires, observation sheet field note and interview guide as the instruments. Moreover, the research subject is an English teacher who teaches at seventh and eighth grades of different schools of Ratnanagar municipality. The result of the research is that the teacher runs nine roles in the classroom. They are as a controller, an assessor, an organizer/manager, a prompter/motivator, a participant, a resource/informer, a facilitator, a demonstrator, and as a guide. There are preeminent roles which are most applied by the teacher, such as teacher as a controller and teacher as an assessor. It is shown by the result of students’ responses in the questionnaire, restrictive questions; 77 percent and 68 percent, and free answer questions; 68 percent and 100 percent, which was also found in the time the researcher did the observation. On the contrary, the teacher’s roles as a prompter and as a resource have not been played maximally by the teacher.